2014
DOI: 10.1016/j.bpj.2014.09.029
|View full text |Cite
|
Sign up to set email alerts
|

FRET-Based Trilateration of Probes Bound within Functional Ryanodine Receptors

Abstract: To locate the biosensor peptide DPc10 bound to ryanodine receptor (RyR) Ca(2+) channels, we developed an approach that combines fluorescence resonance energy transfer (FRET), simulated-annealing, cryo-electron microscopy, and crystallographic data. DPc10 is identical to the 2460-2495 segment within the cardiac muscle RyR isoform (RyR2) central domain. DPc10 binding to RyR2 results in a pathologically elevated Ca(2+) leak by destabilizing key interactions between the RyR2 N-terminal and central domains (unzippi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…Thus, minimal alterations of the native RyR structure are required for these FRET measurements. At the core of our protocol is the geometrical method termed trilateration to determine the relative location of a site by measuring distances from several well-distributed donor coordinates on FKBP, which we have defined using molecular modeling and simulated annealing (Svensson et al, 2014). These optimizations of donor positions on FKBP, combined with the well-established binding location and orientation of FKBP on RyR1 (Cornea et al, 2010; 2009; Samsó et al, 2006) provided the best available accuracy and precision for these trilaterations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, minimal alterations of the native RyR structure are required for these FRET measurements. At the core of our protocol is the geometrical method termed trilateration to determine the relative location of a site by measuring distances from several well-distributed donor coordinates on FKBP, which we have defined using molecular modeling and simulated annealing (Svensson et al, 2014). These optimizations of donor positions on FKBP, combined with the well-established binding location and orientation of FKBP on RyR1 (Cornea et al, 2010; 2009; Samsó et al, 2006) provided the best available accuracy and precision for these trilaterations.…”
Section: Discussionmentioning
confidence: 99%
“…Consistency between measurements using different probes indicated that the FRET-derived distances are accurate. This implies that FRET is insignificantly affected by probe orientation, probably because donors and acceptors undergo isotropic dynamics that are fast relative to the donor fluorescence lifetime (several ns) (Svensson et al, 2014). This approach will be expanded in future studies to localize other His-tagged positions in the proximity of RyR-bound D-FKBP donor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative FRET-based method has been developed that relies on RyR modulator proteins labeled with donor and acceptor probes; binding of these molecules to RyR allows FRET measurements without affecting RyR structure (1,4,5). Two major RyR modulators have been studied, i.e., FK506 binding protein (FKBP), which promotes the closed channel conformation, and calmodulin (CaM), which exerts distinct Ca 2þ -dependent functional effects on the RyR1 and RyR2 channels.…”
mentioning
confidence: 99%
“…The work by Svensson et al (1) is an in-depth analysis of binding of DPc10 to RyR2 in ventricular myocytes. The cells were detergent-permeabilized and loaded with FKBP labeled at five distinct sites with Alexa Fluor FRET donors, and DPc10 labeled with a FRET acceptor at its N-terminus.…”
mentioning
confidence: 99%